2022
DOI: 10.1002/hsr2.881
|View full text |Cite
|
Sign up to set email alerts
|

Effects of SARS‐CoV‐2 infection and COVID‐19 pandemic on menstrual health of women: A systematic review

Abstract: Background: The menstrual cycle in women is the main indicator of their reproductive health which is affected by the ongoing coronavirus disease 2019 pandemic. This review aims to summarize the effects of the COVID-19 infection and the global pandemic on the menstrual health of women. Methods:The literature search was conducted in PubMed, Cochrane library, and Google Scholar using keywords "COVID-19," "Menstrual Cycle," "Menstrual Cycle Irregularities," "Amenorrhea," "Polymenorrhea," and "Dysmenorrhea." The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
2
5
1
Order By: Relevance
“…These included changes in menstrual cycle length, the duration of menses, and changes in premenstrual symptoms. Similar findings were confirmed by other studies [5,15,16], but some authors, however, were in contrast with our findings [5,17].…”
Section: Resultssupporting
confidence: 83%
“…These included changes in menstrual cycle length, the duration of menses, and changes in premenstrual symptoms. Similar findings were confirmed by other studies [5,15,16], but some authors, however, were in contrast with our findings [5,17].…”
Section: Resultssupporting
confidence: 83%
“…It is known that menstrual cycle disorders have increased in women due to increased stress and anxiety during the pandemic. A systematic review reported an increase in menstrual symptoms and a prolongation of the menstrual cycle length in women who had had COVID-19 26 . Ozimek et al 27 reported that increased menstrual irregularities with the pandemic were associated with women’s increased stress levels.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have reported on menstrual cycle disruption during the pandemic [14] , [57] , [66] , [67] , [68] , [69] , [70] , [71*] , [72] , [73] , [74] , [75*] . Two recent systematic reviews have utilised data from the highest quality studies to characterise the relationship between the pandemic and menstrual disturbance [76,77] . A systematic review and meta-analysis incorporating data from six studies, found a significant association between lockdown and changes in the menstrual cycle for 21729 women of reproductive age [76] .…”
Section: The Impact Of the Covid-19 Pandemic On Female Reproductive H...mentioning
confidence: 99%
“…A systematic review and meta-analysis incorporating data from six studies, found a significant association between lockdown and changes in the menstrual cycle for 21729 women of reproductive age [76] . Similarly, the second systematic review which included data from thirteen studies, found that menstrual disorders were a more common during the pandemic as compared to pre-pandemic, and that women affected by pandemic-related stress were more prone to changes in the duration of their menses, and reported increased rates of dysmenorrhoea and heavier menstrual bleeding [77] . A Hungarian study found no association between vaccination or infection and menstrual cycle changes, but found that menstruation length increased whilst regularity of the menstrual cycle decreased during the peak of the pandemic and this correlated with the severity of depression [57] .…”
Section: The Impact Of the Covid-19 Pandemic On Female Reproductive H...mentioning
confidence: 99%